ANALISIS LEGALITAS KUTIPAN AKTA NIKAH WALI PERNIKAHAN OLEH SAUDARA SE IBU DI KANTOR URUSAN AGAMA KECAMATAN ANGKOLA BARAT - Simbolon, Sahron (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2023)
A marriage certificate excerpt is a card as the identity of a married couple. This marriage certificate quote is also equipped with a chip which functions to protect the card from counterfeiting. Excerpts from marriage certificates can only be owned by couples whose marriage is officially registered with the government by registering themselves first. Recently, there have been many problems related to the legality of extracting marriage certificates, such as what happened at the West Angkola District Religious Affairs Office where extracts of marriage certificates were issued with the mother's sibling's marriage guardian. This research aims to find out the practice of marriages with maternal relatives, what is the legality of quoting the marriage certificate of marriage guardians by maternal relatives, and what is the perspective of Islamic law regarding marriages with maternal relatives at the West Angkola District Religious Affairs Office. This research is classified as a descriptive research type. Data was collected using interview techniques and documentation. The results of the data analysis found that the practice of marriages with mother's sibling marriage guardians at the West Angkola District Religious Affairs Office was carried out with an element of misunderstanding regarding the determination of the marriage guardian, and an element of deliberate intention on the part of the bride to determine the marriage guardian of her mother's brother by changing the surname in his name. The marriage guardian is written in the marriage certificate excerpt in the name of Endi Pasaribu, while his real name is Endi Siregar. The legality of the quotation from the marriage certificate of the marriage guardian by the mother's sibling at the West Angkola District Religious Affairs Office, reviewing state law, is still declared valid, because the status of the guardian written on the quotation from the marriage certificate is that of a sibling. Meanwhile, according to Islamic law, the legality of the quotation of the marriage certificate is invalid, because in reality the marriage guardian is Romaida Pasaribu's mother's brother. The review of the law regarding marriage with a marriage guardian by the mother's brother is based on marriage law, the compilation of Islamic law, and on the study of Islamic jurisprudence. Determines that in accordance with the position of the guardian a marriage can be declared invalid and it is mandatory to carry out a remarriage by appointing a legal guardian of the marriage, whether he is a guardian of the lineage or a guardian of the judge.